Truth-Telling in Library Land: In Defense of Emancipatory and Justice-Based Frameworks in Library and Information Science - Amber Matthews; Jamillah R. Gabriel (The Political Librarian, 2025)
In recent years, library and information science (LIS) has increasingly demonstrated a professional commitment to anti-oppression and related concepts of diversity, equity, and inclusion (DEI). Yet despite a growing body of literature underscoring their importance to the field and its communities, a substantial divide remains between the everyday workings of librarianship and the enactment of anti-oppression and DEI praxis. This paper addresses this gap by contextualizing justice-based approaches for LIS and argues that the field must move beyond performative DEI commitments toward structurally embedded praxis rooted in critical race theory and anti-oppression frameworks. It also examines white privilege in the workplace, its impact on DEI initiatives, and the harm experienced by library workers from equity-deserving groups. Drawing on lived experience and interdisciplinary scholarship, the paper offers practical entry points for dismantling systemic inequities and situates DEI within broader emancipatory movements.
Keywords: LIS; DEI; library and information science; diversity; equity; inclusion; equity-deserving; emancipatory; social justice; anti-oppression; praxis; white privilege; workplace environment